The Laboratory Role in anti-TNF Biological Therapy Era. (2nd April 2020) - Grossi, Valentina; Gulli, Francesca; Infantino, Maria; Stefanile, Annunziata; Napodano, Cecilia; Benucci, Maurizio; Pocino, Krizia; Li Gobbi, Francesca; Damiani, Arianna; Di Pino, Antonella; Manfredi, Mariangela; Marino, Mariapaola; et al.
ABSTRACT: Along years, the advent of biological therapy widely modified treatment of rheumatic diseases and other disorders. However, many agents may elicit in anti-drug antibodies (ADAbs) upon consecutive infusions, with a loss of response. For the right strategy of a personalized medicine, the therapeutic monitoring of TNF-α inhibitors and ADAbs represents an important effort in diagnostic–therapeutic pathway, to improve overall patient management and favoring an appropriate clinical approach. A raising number of diagnostic tests have been designed to elucidate the efficacy and/or safety of a specific drug or class of drugs for a targeted patient's group. Our paper reviewed the current understanding of the immunogenicity of biological drugs employed in the treatment of inflammatory diseases underlying the laboratory role.